From Skills to Selves: Recycling "Soviet DIY" in Post-Soviet Russia - Vasilyeva, Zinaida (Neuchâtel, 2019)
This thesis explores a particular phenomenon of everyday material culture, namely “do-it-yourself”, which is routinely referred to in contemporary Russian (post-Soviet) society as a “Soviet” phenomenon. The tension between DIY as a combination of social practices and material facts on the one hand, and public discourses that (re)interpret it on the other, constitutes the central axis of the research. The starting point of this investigation is an observation made while doing fieldwork in 2011-2013: while practices of making, remaking and repairing material objects remain widespread in contemporary Russian society, many of the interlocutors around these practices display a complex mixture of enthusiasm, pride, bewilderment and even shame regarding DIY objects and the skills required to produce them. To understand this ambivalence, the author follows DIY-discourses, objects and their makers to different venues: individuals’ homes, archives of Soviet-period popular technical journals, amateur associations, museums and art galleries. Combining historical investigation with ethnographic research and pursuing the analysis of different sources (interviews, archival documents, literary texts, films, exhibitions and contemporary art works), the author demonstrates the ways in which meanings and values attributed to DIY practices and skills under the Soviet order have been challenged due to the enormous shifts that Soviet citizens experienced after the fall of the Soviet empire. “DIY” is approached, therefore, as both a social and material phenomenon in its own right, and as an analytical tool: a prism through which to analyze Soviet modernity and post-Soviet transformations. The author argues that while manual knowledge and skills and “low” and “slow” technologies were smoothly incorporated into the ideology, institutions and economic thinking of the Soviet modern project and, moreover, promoted by the state as a means to self-realization, the rapid and drastic social and economic transformations of the late 1980s-1990s resulted in a reinterpretation of popular technical culture in terms of “poverty” and “technological backwardness”. Cette thèse explore un phénomène particulier de la culture matérielle quotidienne, à savoir le bricolage / « do-it-yourself » (DIY), qui est souvent référé dans le contexte contemporain russe comme un phénomène « soviétique ». La tension entre les DIY comme pratiques sociales et faits matériels et les discours qui les interprètent constitue l’axe principale de la recherche. Le point de départ de ce travail est une observation faite pendant la recherche de terrain menée en 2010-2013 : bien que les pratiques de bricolage, de récupération et de rénovation des objets restent courant dans la société contemporaine russe (post-soviétique), beaucoup de participants de l’enquête montraient un mélange complexe d’émotions composé d’enthousiasme, de fierté, de perplexité mais aussi de honte quant aux objets bricolés et aux savoir-faire liés à leur production. Pour comprendre cette attitude ambivalente, l’auteur suit les discours, les objets et les pratiquants de DIY et mène sa recherche sur différents terrains : dans les appartements personnels, dans les archives des revues techniques populaires soviétiques, dans les associations d’amateurs, dans les musées et dans les galeries d’art. Tout en combinant l’approche historique avec une enquête ethnographique, l’auteur fonde son analyse sur une variété de sources : entretiens, archives, textes littéraires, films de fiction, expositions et œuvres d’art contemporain, et montre comment les significations et les valeurs attribuées aux pratiques et savoir-faire relevant du DIY dans le contexte soviétique ont été perturbées suite aux changements sociaux et économiques extraordinaires vécus par les citoyens après la chute de l’empire soviétique. Ainsi, le concept de « DIY » fonctionne dans le présent travail dans deux sens : pour décrire un phénomène social et le matériel de bricolage tel qu’il est, et comme un instrument analytique : un prisme pour analyser la modernité soviétique et les transformations post-soviétiques. L’auteur avance que tandis que les compétences et savoir-faire manuels et les technologies « low » et « slow » faisaient partie intégrante de l’imaginaire, des institutions et de la pensée économique dans le contexte du projet moderne soviétique et, plus, étaient promus par l’État comme moyen de valorisation de soi, les transformations rapides de la fin des années 1980-1990 ont entrainé une réinterprétation de la culture technique populaire en termes de la « pauvreté » et de « retard technologique »
Doctoral thesis, University of Neuchâtel, Faculty of Arts and Humanities, Institute of Anthropology / Doctorat, Université de Neuchâtel, Faculté des lettres et sciences humaines, Institut d'ethnologie - TH 2777 Thèse soutenue le 22 mai 2019 à l’Université de Neuchâtel
Keywords: do-it-yourself; DIY; Russia; Soviet Union; post-Soviet transformations; modernity; national stereotype; popular technical knowledge; amateurism; crafts; making; memory; cultural recycling; cultural intimacy; self-activity; subjectivity bricolage; do-it-yourself; DIY; Russie; Union Soviétique; transformations post-soviétiques; modernité; stéréotype national; connaissance technique populaire; amateurisme; savoir-faire; mémoire; recyclage culturel; cultural intimacy; actualisation de soi; subjectivation